Reimagining doctoral success for "non-traditional students": A phenomenological inquiry into the experiences of emerging researchers - Mthombeni, Z. M. (South African Journal of Higher Education, 2024)
Against the backdrop of a transforming doctoral education landscape and the emergence of non-traditional doctoral students, this article investigates strategies to promote the success of students balancing academic studies and their careers. Prevailing discussions on doctoral success strategies have often centred on “traditional” doctoral students. This article examines the doctoral success challenges confronted by “non-traditional” doctoral candidates who pursue higher education at different stages of their lives, often juggling such with work and family or other responsibilities. The study was informed by Ward and Brennan’s model to analyse the compatibility of student-doctoral education. This framework introduces the concept of student-doctoral fit that asserts that non-traditional students achieve optimal success when there is alignment between the student’s values and those upheld by their organization and social structure. Therefore, doctoral success for non-traditional students lies in the alignment of three main spheres, namely, the 1) student-doctoral environment, 2) student vocation, and 3) the student-doctoral culture. In-depth semi-structured interviews were conducted with 15 non-traditional doctoral students employed by a research organization. The findings underscore the intricacies of balancing academic and professional demands, shedding light on the challenges arising from the lack of integration between academic work and doctoral pursuits. They highlight the need to challenge the conventional separation of these facets. Notably, participants highlighted that they received more substantial academic training and support from the research organization and work mentors, emphasizing the variable nature of support by university supervisors. Given that the majority of challenges reported revolve around the fit between the student-doctoral culture and environment, it is recommended that research organizations and universities collaborate and establish robust support structures. This collaborative approach is essential to ensure academic success and facilitate non-traditional doctoral students’ smoother transition into professional careers